Debatable of Indonesian Citizens' Rights and Obligations Regarding the Covid-19 Vaccination Policy - Faizal Saman (Universitas Negeri Gorontalo, 2022)
The purpose of this study is to examine the rights and obligations of Indonesian citizens regarding vaccination. This research uses a type of normative legal research with a statute approach. Collect data by grouping and reviewing regulations, library materials, books, and other sources related to problems in this study. The results showed that polemics that led to pros and cons related to vaccination were caused by several factors such as vaccines being new, the safety of vaccines that cannot be passed, and the sanctions imposed on those who refuse vaccines. The pro-life community considers vaccination to be an obligation and the contras think that the imposition of vaccination is in line with the right to health. There are several variables for the reason for the vaccination policy to be implemented, namely the state in a state of emergency, namely in a pandemic crisis, and subsequently related to the human obligation to respect the human rights of others (the right to the health of others). Thus, the problem of legal certainty from the implementation of vaccination is an obligation of Indonesian citizens.